Анализ теплообменных систем установок газификации нефтеперерабатывающих производств - Товажнянский, Леонид Леонидович; Капустенко, Пётр Алексеевич; Перевертайленко, Александр Юрьевич; Бухкало, Светлана Ивановна; Арсеньева, Ольга Петровна (НТУ "ХПИ", 2011)
The heat exchangers systems of big gasification plants fueled by refinery residues and wastes are discussed. The main features of such plants with power generation are underlined. The essential ways of effectiveness increasing based on heat exchangers systems enhancement are formulated for integrated gasification units with combined cycle of power generation (IGCC).
Keywords: энергоносители; топливо; твердые бытовые отходы; углеродсодержащие отходы; газификация; нефтекокс; теплообменники